2005
DOI: 10.1002/prot.20644
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary plasticity of protein families: Coupling between sequence and structure variation

Abstract: In this work we examine how protein structural changes are coupled with sequence variation in the course of evolution of a family of homologs. The sequence-structure correlation analysis performed on 81 homologous protein families shows that the majority of them exhibit statistically significant linear correlation between the measures of sequence and structural similarity. We observed, however, that there are cases where structural variability cannot be mainly explained by sequence variation, such as protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 44 publications
9
42
0
Order By: Relevance
“…The trend indicates that, in the case of the HADSF, the sequence diverges to a greater extent than does the structure. This deduction is consistent with the findings from earlier studies of single domain protein families (14)(15)(16).…”
Section: Resultssupporting
confidence: 93%
“…The trend indicates that, in the case of the HADSF, the sequence diverges to a greater extent than does the structure. This deduction is consistent with the findings from earlier studies of single domain protein families (14)(15)(16).…”
Section: Resultssupporting
confidence: 93%
“…Recently, it was shown that AmVg is very enriched in replacement polymorphism (Kent et al, 2011). We notice that this polymorphism does not apply to the polyserine tract, which as a connector structure could be an ideal site for replacements (Panchenko et al, 2005). Sequence comparison across taxa suggests that the domain connector may be elongated in insects or possibly more broadly in Protostome animals, but serine residues are not present in all of these elongated connector sequences in insects, for example in the louse Pediculus humanus.…”
Section: Discussionmentioning
confidence: 77%
“…Five outliers were located in coils (Table1). Loops have more evolutional plasticity than b-sheets or -helices (Panchenko et al, 2005), which makes these regions more difficult to model accurately by homology, as their sequence differs from the template structure. Our electrostatic map of the model shows a patch of positively charged residues on the b-sheets (Fig.5B).…”
Section: A Positively Charged Patch a Lipophilic Cavity And An Indicmentioning
confidence: 99%